2018
DOI: 10.1007/s11664-018-6391-6
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of Relative Importance of Stress and Stress Gradient in Whisker Growth in Sn Coatings

Abstract: Here, we study the role of stress state and stress gradient in whisker growth in Sn coatings electrodeposited on brass. The bulk stress in Sn coatings was measured using a laser-optics based curvature setup, whereas glancing angle X-ray diffraction was employed to quantify the surface stress; this also allowed studying role of out-of-plane stress gradient in whisker growth. Both bulk stress and surface stress in Sn coating evolved with time, wherein both were compressive immediately after the deposition, and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Hence, the net diffusion is expected to occur along the path of the steepest hydrostatic stress gradient. The importance of both in-plane and out-of-plane stress gradients has been proposed and indeed observed experimentally 52,61,[80][81][82] and numerically through simulations. 83,84 Microdiffraction studies have shown that the stress distribution in the Sn coating is inhomogeneous, with grain-to-grain stress variation.…”
Section: Role Of Stress-field Anisotropy In Sn Coatings In Mass Transport For Whisker Growthmentioning
confidence: 76%
See 1 more Smart Citation
“…Hence, the net diffusion is expected to occur along the path of the steepest hydrostatic stress gradient. The importance of both in-plane and out-of-plane stress gradients has been proposed and indeed observed experimentally 52,61,[80][81][82] and numerically through simulations. 83,84 Microdiffraction studies have shown that the stress distribution in the Sn coating is inhomogeneous, with grain-to-grain stress variation.…”
Section: Role Of Stress-field Anisotropy In Sn Coatings In Mass Transport For Whisker Growthmentioning
confidence: 76%
“…Another important driving force for whisker growth is mechanically applied stress on the Sn sample. Numerous studies have investigated the application of mechanical stress using different loading devices, such as a clamping fixture, 21,36,58 three-point or four-point bending [59][60][61] of Sn-coated strips, micro-indentation, [62][63][64][65] and in situ nanoindentation. 66,67 Fisher et al, 21 using a ring clamp (shown in Fig.…”
Section: Externally Applied Mechanical Stressmentioning
confidence: 99%